2009
DOI: 10.1016/j.bbamem.2009.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a C-terminal peptide of Bos taurus diacylglycerol acyltransferase 1 with model membranes

Abstract: Diacylglycerol acyltransferase 1 (DGAT1) catalyzes the final and dedicated step in the synthesis of triacylglycerol, which is believed to involve the lipids oleoyl coenzyme A (OCoA) and dioleoyl-sn-glycerol (DOG) as substrates. In this work we investigated the interaction of a specific peptide, referred to as SIT2, on the C-terminal of DGAT1 (HKWCIRHFYKP) with model membranes made with OCoA and DOG in Langmuir monolayers and liposomes. According to the circular dichroism and fluorescence data, conformational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…29 The spectrum in methanol exhibited a blue shift to 340 nm for the tryptophan emission, indicating an organized structure. 29 30 Normally, the interaction between a chromophore and liposomes causes a blue shift and quenching in the spectrum, 31 which indeed occurred for the peptide incorporated in the liposomes. The maximum appeared at 343 nm, similarly to p17-1 in methanol, from which one infers that the peptides are structured in the liposomes.…”
Section: Resultsmentioning
confidence: 98%
“…29 The spectrum in methanol exhibited a blue shift to 340 nm for the tryptophan emission, indicating an organized structure. 29 30 Normally, the interaction between a chromophore and liposomes causes a blue shift and quenching in the spectrum, 31 which indeed occurred for the peptide incorporated in the liposomes. The maximum appeared at 343 nm, similarly to p17-1 in methanol, from which one infers that the peptides are structured in the liposomes.…”
Section: Resultsmentioning
confidence: 98%
“…Meanwhile, other studies with DGAT1 from mice suggested that the N-terminal segment is able to specifically bind to different acyl-CoAs [15]. Bovine DGAT1 shares a conserved region with the ACAT enzymes [16], which also suggests a potential binding region for this substrate. Both these binding sites are proposed to lie within an extramembranous loop of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…involving changes in peptide conformation (B). Reproduced with permission from reference [37]. A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Therefore, in order to determine DGAT1 regions involved in substrate binding, specific regions of the protein were synthesized. Talhari and coworkers studied the peptide NIPVHKWAIR HFYKP, referred to as SIT2, on the C-terminal of DGAT1 [37]. The choice of this region was due to the presence of a putative diacylglycerol binding domain.…”
Section: Accepted Manuscriptmentioning
confidence: 99%